PENGEMBANGAN KOMIK DIGITAL BERBASIS KERAGAMAN BUDAYA PADA PEMBELAJARAN SUMBER ENERGI KELAS IV DI SEKOLAH DASAR - Indah Putri Danyati; M. Jaya Adi Putra; Guslinda Guslinda (STKIP Pesisir Selatan, 2022)
This study aims to produce digital comic media based on cultural diversity in learning energy sources class IV theme II in elementary schools. This type of research is development research (R&D) using the ADDIE development model (Analysis, Design, Development, Implementation and Evaluation). The data in this study were obtained using a questionnaire (questionnaire). The results of the validation carried out by validators and practitioners on digital comic media consisting of 6 aspects of the assessment got an average score of 89.75% with a very valid category. The validation carried out by media experts got a score of 92.31%, the validation carried out by material experts got a score of 86.54%, the validation carried out by linguists got a score of 99.04%, the validation carried out by practitioner I got a score of 82.69 %, and the validation carried out by practitioner II got a score of 93.27%. The subjects of this study were fourth grade elementary school students at SDIT Raudaturrahmah Pekanbaru. The results of the one-to-one trial obtained an average score of 84% by indicating a very feasible category. The results of the limited trial got an average score of 84.81% with a very decent category. Based on the description above, it can be concluded that comics media based on cultural diversity in class IV energy source learning in elementary schools are appropriate for elementary school students.